Assessment of root resorption on lateral incisors after primary canine extraction treating mesioangular displaced permanent canines: a randomised controlled trial - Helal, Narmin; Naaman, Reem; Alamoudi, Najlaa; El-Housseiny, Azza; Jadu, Fatima (Frontiers in Dental Medicine, 2025)
Aim Root resorption (RR) of the adjacent maxillary lateral incisors is considered the most common complication of displaced maxillary canines. The aim of this study was to assess the effect of interceptive extraction of the primary canines on the condition of the roots of permanent neighbouring teeth to mesioangular displaced canines (MDC). In addition, this study aimed to investigate the relationship between the position of the unerupted canine and the risk of RR in adjacent lateral incisors. Design Randomised controlled clinical trial. Methods Eighty-five patients 9–12-year-old with MDC were allocated equally to either an extraction group (EG) or a control group (CG). Of the sample, 33 were males (38.8%), and 52 were females (61.2%). Among this sample, 81 canines (51.9%) were buccally displaced, 34 canines (21.8%) were palatally displaced, and 41 canines (26.3%) were mid-alveolar. All subjects underwent cone-beam computed tomography examination to determine the presence, stage, and level of lateral incisor root resorption (RR). Measurements were performed at T0 and repeated at a 12-month follow-up (T2). Results & statistics Root resorption (RR) was present in 28.2% of lateral incisors at the baseline assessment (T0) and exhibited a significant increase at the 12-month follow-up (T12). This marked increase in resorption severity was evident between T0 and T12 (P = 0007), regardless of group allocation. There was a significant increase in the degree of resorption between T2 and T0, with a mean difference equals to 0.31 (0.73), P < 0.0001. While there was no statistically significant difference in resorption levels between the extraction and control groups at T0 (P = 0.11), RR occurred more frequently with midalveolar (34.1%) and palatal (32.3%) displacements than with buccal displacements (23.5%). Severe resorption was observed more frequently in cases involving palatally displaced canines within both groups, but it did not reach statistical significance. Conclusions Lateral incisor root resorption (RR) progressed significantly within a 12-month period irrespective of treatment modality. RR occurred more frequently with midalveolar and palatal displacement with a trend towards increased RR severity in cases with palatally displaced canines. Early clinical evaluation and consistent monitoring is essential for early detection and potential intervention in patients with mesioangular canine displacement.